Inoculum sizes of locally isolated phototrophic bacterium on the utilization of palm mill effluent - Sujjat Al Azad; Sitti Raehanah Muhammad Shaleh (SCIENCEDOMAIN international, 2015)
To produce Rhodobacter sphaeroides strain UMSPSB3 biomass with the reduction of chemical oxygen demand (COD) from palm oil mill effluent. Locally isolated phototrophic bacterium with different inoculum levels were used in Palm Oil Mill effluent (POME). Collected POME was characterized before used as substrate. Inoculum of bacterium was grown in synthetic media and 48 hours inoculum was used to utilize the substrate. Biotechnological laboratory, Borneo Marine Research Institute, University Malaysia Sabah, Kota Kinabalu, Sabah, Malaysia, between February 2014 to April 2014. Growth characteristics of bacterium Rhodobacter sphaeroides strain UMSPSB3 was monitored at different light intensities. Later phototrophic bacterium Rhodobacter sphaeroides strain UMSPSB3 was grown in settled non-sterilized Palm Oil Mill effluent (POME). The growth characteristics of bacterium in term of dry cell weight and total carotenoids production, and reduction of COD were compared using 10%, 20% and 30% (v/v) levels of inoculum developed in synthetic 112 media.